Ancillary services in Indian power system – Implementation challenges - Wadi, Sagar A.; Verghese, Shamreena; Balaji, V.; Suresh, V.; Anbunesan, G. (Indian Journal of Power and River Valley Development, 2022)
Reserve regulatory ancillary service (RRAS) was implemented on 12th April 2016 in Indian power system to empower the system operator to maintain the frequency in IEGC band, regulate line loadings, loss of generation or load, etc. This paper discusses the challenges in implementation of RRAS.